Bioactive compounds, antioxidant activity and sensory properties of Tarhana, a traditional fermented food, enriched with pickling herb (Echinophora tenuifolia L.). (19th February 2021) - Ghafoor, Kashif; Al‐Juhaimi, Fahad; Özcan, Mehmet Musa; Babiker, Elfadıl E.; Ahmed, Isam A. Mohamed; Alsawmahi, Omer N.
Summary: The addition of pickling herb ( Echinophora tenuifolia L.; PHET) resulted in increase in the total phenolic and flavonoid contents in Tarhana in both free and bound fractions' extracts. The antioxidant activity of Tarhana containing 2%, 6% and 18% PHET was 81.45–81.72% in bound fraction whereas in free fraction it was up to 88.27% (6% PHET). The gallic acid contents of Tarhana with PHET in free fraction were between 0.49 mg L −1 (10%) and 2.75% (14%) and that in bound fraction varied between 0.36 mg L −1 (10%) and 3.61 mg L −1 (18%). Statistically significant differences (with control) were observed among the contents of individual phenolic compounds in free and bound fractions of Tarhana depending on PHET concentrations. The addition of higher PHET contents in Tarhana showed negative effects hence, a low concentration (2%) of PHET is recommendable for Tarhana with enhanced nutritional properties. Abstract : Total phenolic, total flavonoid and antioxidant activity of tarhana samples containing pickling herb (PH)